Systematics and integrative taxonomic revision of the tribe Scopulini Duponchel, 1845 in Iran (Lepidoptera: Geometridae: Sterrhinae) - Wanke, Dominic; Hausmann, Axel; Lee, Kyung Min; Murillo-Ramos, Leidys; Sihvonen, Pasi; Rajaei, Hossein (Zootaxa, 2023)
The Iranian taxa of the tribe Scopulini are taxonomically revised. The systematic positions of the genera Cinglis Guenée, 1858, Glossotrophia Prout, 1913, Pseudocinglis Hausmann, 1994 and Scopuloides Hausmann, 1994, with uncertain validity and/or position within the tribe Scopulini Duponchel, 1845 (Lepidoptera: Sterrhinae), are further elucidated by use of one mitochondrial and up to nine protein-coding nuclear gene regions. Available type specimens of the described species and more than 2,600 additional specimens were morphologically investigated. In addition, over 400 genitalia preparations were made and examined together with distribution data and DNA barcodes. As a result of the multi-gene analysis, the genera Cinglis stat. rev. and Scopuloides stat. rev. are re-validated at the genus level. The genus Pseudocinglis syn. nov. is regarded as a junior synonym of the genus Cinglis stat. rev. and Glossotrophia syn. nov. is regarded as a junior synonym of the genus Scopula. Cinglis eurata (Prout, 1913) comb. nov. and Cinglis benigna (Brandt, 1941) comb. nov. are combined with the genus Cinglis. Additionally, Cinglis benigna amseli (Wiltshire, 1967) syn. nov. is regarded as a synonym of C. benigna. Scopula adulteraria (Erschov, 1874) stat. nov. is raised from subspecies to species rank; Scopula iranaria Bytinski-Salz & Brandt, 1937 syn. nov. is synonymized with S. flaccidaria (Zeller, 1852); S. transcaspica taftanica Brandt, 1941 syn. nov. is synonymized with S. transcaspica Prout, 1935; S. diffinaria asiatica (Brandt, 1938) syn. nov. is synonymized with S. diffinaria (Prout, 1913) and Glossotrophia bullata Vojnits, 1986 syn. nov. is synonymized with Scopula sacraria ariana (Ebert, 1965). The female genitalia of Scopula lactarioides Brandt, 1941 are described and illustrated for the first time. In total, the presence of 33 species of Scopulini in Iran is confirmed. Wing patterns, male and female genitalia and diagnostic characters of most Iranian Scopulini species are depicted and their distribution ranges are mapped.